IMPACT OF CASH TRANSFER ON POVERTY - Deden Ferry Kurniawan; Hera Susanti (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2018)
This research aims to generate empirical evidence on the impact of cash transfers on Poverty on households in Indonesia, using the Indonesian Family Life Survey (IFLS) panel data in 2007 and 2014, and the method of Difference-in-differences with propensity score matching. This study estimates the impact of relief and benefits that do not receive assistance on Poverty. Results are expected to find that the provision of assistance (cash transfers) has a significant impact on poverty in terms of beneficiaries and who does not receive assistance, or viewed from a total of two (beneficiaries and who are not receiving assistance). It is found that the provision of assistance to the people who were targeted as shown to improve the welfare of beneficiaries, but have not been able to exceed the group that did not receive aid. JEL Classification: I31, I32, I38Keywords: Cash transfer, Difference-in-differences, Poverty, Propensity Score Matching